1998
DOI: 10.1152/ajpendo.1998.274.1.e13
|View full text |Cite
|
Sign up to set email alerts
|

Production and utilization of amino acids by ovine placenta in vivo

Abstract: Uterine and umbilical uptakes of plasma amino acids were measured simultaneously in eighteen singleton pregnant ewes at 130 ± 1 days gestation for the purpose of establishing which amino acids are produced or used by the uteroplacenta under normal physiological conditions and at what rates. The branched-chain amino acids (BCAA) had uterine uptakes significantly greater than umbilical uptakes. Net uteroplacental BCAA utilization was 8.0 ± 2.5 μmol ⋅ kg fetus−1 ⋅ min−1( P < 0.005) and represented 42% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
73
3
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 17 publications
7
73
3
2
Order By: Relevance
“…Discussions on uteroplacental and fetal uptake of AA can be primarily divided into two areas of interest focusing on either metabolic pathways or transport systems (Battaglia and Regnault, 2001;Jansson, 2001;Fowden et al, 2006). From a metabolic standpoint, previous research has shown consistent uterine and fetal uptakes of essential AA (Chung et al, 1998). Contradictory to previous research we observed an increased uptake for the majority of AA in the fetus compared with the uterus, which resulted in many AA being released from the uteroplacenta.…”
Section: Discussionmentioning
confidence: 57%
“…Discussions on uteroplacental and fetal uptake of AA can be primarily divided into two areas of interest focusing on either metabolic pathways or transport systems (Battaglia and Regnault, 2001;Jansson, 2001;Fowden et al, 2006). From a metabolic standpoint, previous research has shown consistent uterine and fetal uptakes of essential AA (Chung et al, 1998). Contradictory to previous research we observed an increased uptake for the majority of AA in the fetus compared with the uterus, which resulted in many AA being released from the uteroplacenta.…”
Section: Discussionmentioning
confidence: 57%
“…This also included comparisons between essential and non-essential AA, where only limited information is available (e.g. Biolo et al [17]; Chung et al [24]). The data at 1.5 M were similar to those from a comparable intake in an earlier study [10], but were lower for some non essential AA (plasma ILR = 10.34 mmol·h -1 vs. 6.95 mmol·h -1 for glycine, 17.12 mmol·h -1 vs. 12.26 mmol·h -1 for glutamate, 5.43 mmol·h -1 vs. 2.81 mmol·h -1 for aspartate).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of synthesis and inter-conversion varies with species as well as the nutritional and physiological state (e.g. Wolff et al [18]; Chung et al [24]). For sheep, although serine is converted to glycine [41], the converse does not occur ( [42] and unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate is another amino acid that is not significantly taken up by the uterine circulation (2,7). This is accompanied by a net release from the fetus toward the placenta, opposite in direction to the flux of most other amino acids and similar to the net flux of serine into the placenta, suggesting a unique role for both of these two nonessential amino acids (Fig.…”
mentioning
confidence: 99%